Granulomatous Mastitis: A Clinical and Diagnostic Dilemma - Emel Ebru PALA; Sumeyye EKMEKCI; Melis KILIC; Ayberk DURSUN; Gul COLAKOGLU; Cem KARAALI; Mumin EMIROGLU; Mustafa EMIROGLU (Türk Patoloji Dergisi, 2022)

(untitled)
Objective: Granulomatous mastitis (GM) is a challenging inflammatory disorder of the breast. In this study we aimed to present the detailed clinical and morphological features of GM cases, diagnostic clues for specific and idiopathic etiologies, the difficulties in evaluating trucut biopsies, and the results of different therapeutic approaches.